PEMANFAATAN KEMBALI SAMPAH TEMPURUNG KELAPA MENJADI BRIKET - Dery Perayoga; Azam Hatami; Muhammad H Amrullah; Subkhan Subkhan (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
The reuse of coconut shell waste into briquettes is a way to reduce waste in the community and can be one of the livelihoods, because it utilizes coconut shell waste into briquettes which can be done simply, and comes from coconut shell waste that is easily found in the community. Coconut shell waste that is scattered in the community if left unchecked can become a problem, such as: becoming a source of disease and becoming a nest for mosquitoes. This implementation method is carried out in two major stages, namely the design and manufacture of a briquette printing machine from coconut shell waste. The result achieved in this activity is the creation of a briquette printing machine from coconut shell waste with the resulting pellet size of 5 cm x 5 cm x 5 cm. Based on the results and discussion described above, it can be concluded that the working system of the coconut shell briquette printing machine works well and as desired. The suggestion for the development of the next briquette printing machine is to focus on a cutting system that functions as a briquette dough pusher to the required size. This is, with the aim of making it easier for MSMEs and the community in making briquettes from coconut shell waste and being able to increase the productivity of cattle.